Clumped Isotope Calibration Data from Peral et al. 2018, reprocessed as part of a community calibration effort (IEDA: EarthChem Library)
Clumped isotope calibration data from 14 published studies were compiled and reprocessed from the base level (raw voltages or small delta values) using updated IUPAC parameters defining the composition of international standards (VPDB, VSMOW) and 17O fractionation, updated theoretical equilibrium values, and newly calculated acid digestion fractionation (AFF) corrections. This EarthChem dataset archives all reprocessed data originally from Peral et al. (2018, GCA), presented in the synthesis publication.